The relationship between demographics factors and the participation by individual taxpayers in Johor Bahru in the special voluntary disclosure program (svdp) - Zulkapli, Amir arif (2020)
The tax non-compliance issue is a global issue that happens all over the world, including in Malaysia. Tax non-compliance requires tax administrators to identify suitable and appropriate measures to solve this issue. The Malaysian Government decided to launch the Special Voluntary Disclosure Program (SVDP) from 3 November 2018 – 30 September 2019 as an effort to increase the level of tax compliance in Malaysia. The Government and the Inland Revenue Board of Malaysia (IRBM) have set the target for the SVDP to attract one million taxpayers and RM10 billion in total collection and penalty throughout this program. Despite this target, only 286,428 taxpayers (28.6%) participated in this program and RM7.8 billion tax and penalty were raised. There are a lot of room for improvements in future if the same program is to be implemented by the Government. Therefore, the aim of this study is to examine the relationship between demographic factors (age, gender, race, marital status, type of income, source of income) and taxpayers’ behaviour to join the SVDP, involving 200 taxpayers in Johor Bahru through an online survey. Findings show that marital status and type of income are statistically significant and the other four factors are insignificant. Only two of the six hypothesized relationships are supported in this study. From the findings, the IRBM can focus more on both type of income (salary-earners and the self-employed taxpayers) as well as single and married taxpayers in terms of tax education and audit as these groups of taxpayers are indirectly involved in the tax noncompliance issue.